A Tempest of Tea - Faizal, Hafsah (New York : Farrar Straus Giroux, 2024)
Arthie Casimir, a criminal mastermind, transforms her tearoom into an illegal bloodhouse for vampires, but when her establishment is threatened, she forms an unlikely alliance and assembles a misfit crew to infiltrate vampire society and uncovers a world-threatening conspiracy.
Ages 14-18
Grades 10-12
Keywords: Vampires -- Juvenile fiction; Interpersonal relations -- Juvenile fiction; Vampires -- Fiction; Interpersonal relations -- Fiction; Fantasy fiction; Novels